A newly isolated alkaliphilic cyanobacterium for biomass production with direct air CO2 capture. (March 2023) - Gao, Song; Pittman, Kyle; Edmundson, Scott; Huesemann, Michael; Greer, Mattias; Louie, William; Chen, Peter; Nobles, David; Benemann, John; Crowe, Braden
Abstract: Large-scale microalgal biomass production usually relies on concentrated CO2 as the carbon source which is a major logistical and economic challenge because of the required infrastructure and geospatial constraints of siting large algal production facilities close to concentrated CO2 sources. By taking advantage of enhanced CO2 mass transfer within alkaline media due to the reaction between CO2 and OH -, carbon can be directly captured from the ambient air and used by the algae. Achieving such goal requires algal strains that can grow fast under alkaline conditions. In this study, a newly isolated alkaliphilic cyanobacterial strain Cyanobacterium sp. PNNL-SSL1 was characterized for its temperature, pH, and salinity tolerance. The result shows that PNNL-SSL1 could sustain grow at pH above 11.2 but exhibited the highest growth rates at pH below 10.5. The strain is a warm season strain and grows the best at 10 PSU (practical salinity unit). The strain was then evaluated in indoor climate simulation ponds under outdoor-relevant pond cultivation conditions with carbon supplied only through direct air CO2 capture at the culture surface. Two batch culture runs, at slightly different initial pH, exhibited average biomass productivity of 15.2 g m -2 day -1 on ash-free dry weight basis. CO2 was directly captured from the air at an average rate of 21.6 g CO2 m -2 day -1 (78.8 tons ha -1 yr -1 ), contributing 74% of the carbon fixed in the biomass. The results demonstrated that PNNL-SSL1 is a promising strain for biomass production using air CO2 as the carbon source. Graphical Abstract: Carbon mass transfer and equilibrium reactions in culture medium. Due to the slow equilibrium processes at near-neutral pH, air CO 2 is captured at a rate that is too low to support high biomass productivity. Under alkaline conditions, the CO 2 mass transfer rate is enhanced by the fast chemical reaction between CO 2 aq and OH − (red arrows), allowing increased biomass production with direct air CO2 capture . ga1 Highlights: A novel strain of Cyanobacterium sp. PNNL-SSL1 as a candidate for biomass cultivation and direct air capture. The strain exhibits high specific growth rates under alkaline conditions. Biomass is cultivated in alkaline medium in raceway ponds without concentrated CO2 supply. Areal biomass productivity and direct air CO2 capture rate are reported.